The Epidemiology of Fracture in Patients with Acute Ischemic Stroke in Korea - Lee, Kyung Bok; Lee, Jung-Gon; Kim, Beom Joon; Kim, Jun Yup; Lee, Keon-Joo; Han, Moon-Ku; Park, Jong-Moo; Kang, Kyusik; Cho, Yong-Jin; Park, Hong-Kyun; Hong, Keun-Sik; Park, Tai Hwan; et al. (Journal of Korean medical science, 2019)
Patients who survive an acute phase of stroke are at risk of falls and fractures afterwards. However, it is largely unknown how frequent fractures occur in the Asian stroke population. Patients with acute (< 7 days) ischemic stroke who were hospitalized between January 2011 and November 2013 were identified from a prospective multicenter stroke registry in Korea, and were linked to the National Health Insurance Service claim database. The incidences of fractures were investigated during the first 4 years after index stroke. The cumulative incidence functions (CIFs) were estimated by the Gray's test for competing risk data. Fine and Gray model for competing risk data was applied for exploring risk factors of post-stroke fractures. Among a total of 11,522 patients, 1,616 fracture events were identified: 712 spine fractures, 397 hip fractures and 714 other fractures. The CIFs of any fractures were 2.63% at 6 months, 4.43% at 1 year, 8.09% at 2 years and 13.00% at 4 years. Those of spine/hip fractures were 1.11%/0.61%, 1.88%/1.03%, 3.28%/1.86% and 5.79%/3.15%, respectively. Age by a 10-year increment (hazard ratio [HR], 1.23; 95% confidence interval [CI], 1.17-1.30), women (HR, 1.74; 95% CI, 1.54-1.97), previous fracture (HR, 1.72; 95% CI, 1.54-1.92) and osteoporosis (HR, 1.44; 95% CI, 1.27-1.63) were independent risk factors of post-stroke fracture. The CIFs of fractures are about 8% at 2 years and 13% at 4 years after acute ischemic stroke in Korea. Older age, women, pre-stroke fracture and osteoporosis raised the risk of post-stroke fractures.